2015
DOI: 10.1016/j.resconrec.2015.05.016
|View full text |Cite
|
Sign up to set email alerts
|

An industrial ecology approach to municipal solid waste management: II. Case studies for recovering energy from the organic fraction of MSW

Abstract: a b s t r a c tThe organic fraction of municipal solid waste provides abundant opportunities for industrial ecologybased symbiotic use. Energy production, economics, and environmental aspects are analyzed for four alternatives based on different technologies: incineration with energy recovery, gasification, anaerobic digestion, and fermentation. In these cases electricity and ethanol are the products considered, but other products and attempts at symbiosis can be made. The four technologies are in various stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 28 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…The importance of these steps should not be underestimated. Smith et al (2015) provide examples for WTE technologies.…”
Section: Methodology For Attaining Industrial Ecologymentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of these steps should not be underestimated. Smith et al (2015) provide examples for WTE technologies.…”
Section: Methodology For Attaining Industrial Ecologymentioning
confidence: 99%
“…The circled numbers in the figure correspond to the waste management hierarchy (U.S. EPA, 2013). In part two of this work (Smith et al 2015) the Waste-to-Energy process box in Figure 1 will be expanded and various transformations (not only incineration) will be evaluated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The alternatives without burning the feedstock lead to CO2 emission reductions. Residuals are in all cases, however, many opportunities exist for industrial ecology to recycle [60].…”
Section: Municipal Solid Waste As Sustainable Energy Resourcementioning
confidence: 99%
“…The industrial ecology‐based analysis showed that AD has less impact on the environment than fermentation, gasification, and incineration . A conceptual level analysis indicates that gasification, fermentation, AD alternatives lead to positive economic results .…”
Section: Pyrolysismentioning
confidence: 99%